Transcriptome Sequencing of the Endangered Species Elongate Loach (Leptobotia elongata) From the Yangtze River: De novo Transcriptome Assembly, Annotation, Identification and Validation of EST-SSR Markers - Zhang, Yunbang; Gao, Jian; Zhang, Yunhai; Zou, Yuanchao; Cao, Xiaojuan (Frontiers in Marine Science, 2021)
Elongate loach (Leptobotia elongata) is endemic to middle and upper reaches of the Yangtze River in China. Due to overfishing and habitat destruction, this loach has become an endangered species. So far, lack of reliable genetic information and molecular markers has hindered the conservation and utilization of elongate loach resources. Therefore, we here performed an Illumina sequencing and de novo transcriptome assembly in elongate loach, and then developed polymorphic simple sequence repeat markers (SSRs). After assembly, 51,185 unigenes were obtained, with an average length of 1,496 bp. A total of 23,901 expressed sequence tag-simple sequence repeats (EST-SSRs) were identified, distributing in 14,422 unigenes, with a distribution frequency of 28.18%. Out of 16,885 designed EST-SSR primers, 150 primers (3 or 4 base repetition-dominated) were synthesized for polymorphic EST-SSR development. Then, 52 polymorphic EST-SSRs were identified, with polymorphism information contents (PIC) ranging from 0.03 to 0.88 (average 0.54). In conclusion, this was the first report of transcriptome sequencing of elongate loach. Meanwhile, we developed a set of polymorphic EST-SSRs for the loach. This study will provide an important basis, namely genetic information and polymorphic SSRs, for further population genetics and breeding studies of this endangered and economic loach in China.